Comparative Study of Education for Children with Special Needs in Malaysia and Indonesian Primary School - Siti Istiyati; Sri Marmoah; Jenny I. S Poerwanti; Supianto; Sukarno; Hasan Mahfud (Jurnal Penelitian Pendidikan IPA, 2023)
The article aims to compare the implementation of education for children with special needs in primary schools in Malaysia and Indonesia. This study used a descriptive qualitative approach. Data was used using literature studies, observations, and interviews. The subjects used were elementary schools in Surakarta City, Indonesia, and Malaysia. The data is analyzed by means of comparative analysis. The results showed that Indonesia and Malaysia apply the concept of inclusion in the education of children with special needs. In terms of Technology, Malaysia is more advanced by introducing educational Technology such as applications and assistive Technology. This study shows a comparison of education for children with special needs in the two countries, and it is hoped that this study can recommend good practices for the effectiveness and improvement of the quality of education for children with special needs in elementary schools.